FEATURES OF GEOLOGICAL STRUCTURE AND PETROGRAPHIC COMPOSITION OF JIL-QARAKHACH HYPERBASITE PROTRUSIVE MASSIF OF SEVAN–HAKARI OPHIOLITE ZONE (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
The processes that lead to the introduction of ophiolites, it is much easier to associate with the displaced protrusions on deep faults, than with the magmatic intrusion (according to classical concepts) or obduction mechanism (under-hypothes of plate tectonics). The tectonic nature of the contact zone of hyperbasites and limestones (where rocks are deformed, brecciated and mylonitied) and the lack of high-temperature contact metamorphism around ophiolites massif are shown. In addition the article presents the petrographic characteristics of hyperbasites.
Keywords: Jil-Qarakhach protrusive massif; hyperbasite; tectonic contact; Sevan–Hakari ophiolite zone